2019
DOI: 10.21608/zumj.2019.15216.1376
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Job stress and Oxidative stress Biomarkers among Nurses in Zagazig University Hospitals

Abstract: Background: Nursing is highly demanding and stressful profession. Job stress was found to be a stronger predictor of oxidative stress activity causing elevation of blood oxidative biomarkers. This work aimed to improve mental and psychological health of nurses through identification of prevalence of work stress among nurses at Zagazig university hospitals (ZUHs) and assess the association between work stress and blood oxidative biomarkers. Methods: A comparative cross-sectional study was conducted among 40 nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…On the other hand, the administrative control workers are considered not to experience job stress as the brickfield workers due to the less exhausting nature of their work and having fixed day shifts of less than 48 working hours per week. Similar results were obtained by a recent study that showed significantly higher levels of job stress among nurses compared with the administrative controls 31 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, the administrative control workers are considered not to experience job stress as the brickfield workers due to the less exhausting nature of their work and having fixed day shifts of less than 48 working hours per week. Similar results were obtained by a recent study that showed significantly higher levels of job stress among nurses compared with the administrative controls 31 …”
Section: Discussionsupporting
confidence: 90%
“…Similar results were obtained by a recent study that showed significantly higher levels of job stress among nurses compared with the administrative controls. 31 Obviously, all the surrounding workplace conditions in the brick manufacturing industry could favor a considerable status of oxidative stress; however, generally, job or life stress especially chronic stress was found to be a stronger predictor of oxidative stress activity than other established oxidant-promoting factors such as environmental or occupational exposures that could result in elevation of biomarkers of oxidative stress. 32 Moreover, under both normal and pathological conditions, ROS are generated in the cytosol, mitochondria, lysosomes, peroxisomes, and plasma membranes in the human body; their levels can be elevated by stressful conditions such as OS.…”
Section: Discussionmentioning
confidence: 98%
“…MDA and SOD levels among nurses were significantly higher than the office employee group (control). [ 24 ] The study by Yau et al . also agreed with our findings and was aimed at determining the amount of occupational stress as well as stress-inducing factors in the Zhuhai hospital in China.…”
Section: Discussionmentioning
confidence: 99%